Taking English Planning Law Scholarship Seriously - Lee, Maria; Abbot, Carolyn (UCL Press, 2022)
Planning is at the heart of the response to many of the significant challenges of our time, from the climate and environmental crises to social and economic inequalities. It is embedded in, as well as partially constituting, our democratic systems, so that the challenges of democratic decision-making in a complex society cannot be avoided when thinking about planning. Planning law raises some of the most fundamental questions faced by legal scholars, from the legitimacy of authority to the relationship between public and private rights and interests. And yet, planning law has been relatively neglected by legal scholars. The objective of Taking English Planning Law Scholarship Seriously is to create space for planning law scholarship in all of its variety, and for curiosity about law in all of its complexity. The chapters reflect this diversity and complexity, covering a range of the objects of planning (from housing to energy to highways) and a multiplicity of planning tasks and tools (from compulsory purchase to contracting to planning inquiries).